Productivity and proximate analyses of Spirulina (Arthrospira platensis) in different floating water-based photobioreactor designs - Abdul Kader, Mohamed Amar Naqqiuddin (2016)
Various concepts of photobioreactor (PBR) have been discovered scientists around the world. Though, only definite photobioreactor designs would be suitable for growing microalgae in a certain geographical climate outdoor condition. This study focused on developing simple floating water-based photobioreactor (PBR) without any computerized controlled systems. The aim of this study was to identify the chronology in developing best design overall for a photobioreactor. Major part of the design involved the aspect of the structure materials, shape and rigidness, whereas minor parts of the photobioreactors design includes the aeration placement, agitation or mixing, coloration corresponding to the high light intensity, temperature control, the size of the openings for the free exchange of gas and support for stable float on the water. Experiments performed would indicate these simple floating photobioreactors whether there are either significant or insignificant effects on the productivity of Arthrospira platensis (Spirulina) compared to the simple land based PBR especially under tropical climate.In outdoor condition in Malaysia, the weather patterns are extremely unexpected. Weather patterns that usually occurs can be categorized into three namely, first, humid or wet weather that have a high frequency of rain; mixed weather which has average frequency of rain occurrence, overcast with thick cloud layer and also relatively have high light intensity; finally, dry weather having less rain, often exposed to high temperatures and bright sunlight. Floating photobioreactor (PBR) has been designed in two distinct rigid shapes (Octagonal and Cylindrical) built using recycled water bottles, Polyethylene terephthalate (PET).While another form of simple floating PBR was designed more flexible as floating enclosure and was custom made from High Density Polyethylene (HDPE) materials. Simple land based PBR was prepared with High-density Polyethylene (HDPE) plastic bag, (25cm x 50cm). For every minor modification, 10 days of A. platensis cultivation inside all PBRs were conducted with daily monitoring of growth parameters. The expected outcome from this experiment shall anticipate that floating PBRs would gives higher yield in term of biomass dry weight and specific growth rate of cultured A. platensis in comparison of land based PBR. In any case, developing and third world countries could use simple floating PBRs for commercial applications instead of investing on impractical and complicated photobioreactor designs. For proximate analyses, the average total protein content (%) of A. platensis cultured in Cylindrical and Octagonal PBR under dry weather condition was higher significantly (p < 0.05) at 61.18±0.45 and 60.58±0.62 than other PBRs respectively. Total carbohydrate content (%) of A. platensis cultured in Cylindrical PBR (dry weather condition) was significantly (p < 0.05) higher at 26.71±1.43. While the lowest lipid content recorded in Flexible PBR, 0.66 ± 0.579% respectively. Highest scored by Cylindrical PBR, 7.883±0.28 under mix weather condition. The study indicated simple floating photobioreactor system for practical commercial cultivation system. Water based cultivation system has been seen promising compared to land based cultivation system. Several advantages were determined as more dry biomass and productivity of Spirulina were achieved compared to common practice of land based cultivation system. Moreover, this simple enclosed floating photobioreactor system may be an economical starter approach for modern farmers in order to maintain high quality, cleanliness and purity of Spirulina.